Turnover Intention among Public Sector Health Workforce: Is Job Satisfaction the Issue? - JMG, Roslan; AM, Noor Hazilah; B, Nor Filzatun; MO, Azahadi (IIUM Medical Journal Malaysia, 2014)
Introduction: The paper explores turnover intention and job satisfaction among healthcare employees of Ministry of Health (MOH) Malaysia. Methods: A nationwide study was carried out in order to identify dimensions of job satisfaction and turnover intention among public healthcare employees. Data was collected by means of self-administered questionnaire and distributed based on quota sampling. Results: The study shows that public healthcare workforce is generally satisfied with their work (mean 3.45). In addition, medical specialists and assistant medical officers were found to be significantly more satisfied than other job designations. However, intention to resign was high among medical specialists, pharmacists and dentists. A high proportion of medical specialists also had received job offers from the private sector. Conclusion: The findings showed that employee turnover may not necessarily be due to job dissatisfaction, but rather due to demand from the private sector. Findings from the study would assist policy-makers with respect to talent management in public healthcare service.